Comparative Development of Indonesia and Nigeria in the First Two Decades of Democracy: Divergence or Convergence? - Adamu Waziri Babagana (Jurnal Ekonomi dan Studi Pembangunan, 2022)
Indonesia and Nigeria are considered suitable candidates for comparative analysis because of their similarities in natural endowments and geographical attributes, demography, economic structure, sociocultural diversity, and political history. Indonesia began to achieve rapid growth in the 1980s while Nigeria did not. During that period, economic policies in the two countries diverged, and this led to sustained economic growth in Indonesia and prolonged economic decline in Nigeria. However, as the countries transitioned to democratic rule in 1999 following the collapse of authoritarian regimes, some aspects of their political and economic trajectories revealed a trend towards convergence. Using the descriptive comparison of secondary data, the researcher analyzed those converging paths and the areas where the divergence continues. The study concludes that despite exhibiting more signs of convergence and dealing with similar challenges, the impact of initial conditions is likely to influence the developmental efforts in Indonesia and Nigeria.